Tissue inhibitor of metalloproteinase (TIMP)-1 predicts failure of recovery of ejection fraction in acute heart failure with reduced ejection fraction - Tseng, Chih-Hsueh; Huang, Wei-Ming; Chang, Hao-Chih; Yu, Wen-Chung; Cheng, Hao-Min; Chiang, Chern-En; Chen, Chen-Huan; Sung, Shih-Hsien (Open heart, 2024)
BackgroundHeart failure (HF) with improved ejection fraction (HFimpEF) is a recently identified phenotype of HF, which had better cardiovascular outcomes compared with persistent HF with reduced ejection fraction (HFrEF). The present study aimed to investigate the predictive value of tissue inhibitor of metalloproteinase (TIMP)-1 and matrix metalloproteinases-9 (MMP-9) in the recovery of left ventricular ejection fraction (LVEF).MethodsSubjects who presented with acute decompensated HF and reduced LVEF of ≤40% were eligible for this study. HFimpEF was defined by a follow-up LVEF >40% and a ≥10% improvement in LVEF. Overnight fasting N-terminal pro-brain natriuretic peptide (NT-proBNP), MMP-9 and TIMP-1 were measured within 24 hours before discharge. The study participants were followed for up to 5 years.ResultsAmong a total of 91 participants (70.1±16.2 years, baseline LVEF 28.9±7.6%), 19 (20.8%) of them had HFimpEF and 72 (79.2%) had persistent HFrEF at 6 months. The receiver operating characteristic curve analyses showed the area under curve measures for TIMP-1, MMP-9 and NT-proBNP in the prediction of HFimpEF were 0.69, 0.52 and 0.65, respectively. TIMP-1 was negatively correlated with HFimpEF as continuous variables (OR per 1-SD and 95% CI 0.99 (0.98 to 1.00)) and categorical variables (cut-off value 200.68 ng/mL, OR and 95% CI 0.16 (0.05 to 0.54)) after adjustment of confounding factors. During a mean follow-up duration 34.8 months, patients with HFimpEF will have better long-term survival than those with persistent HFrEF.ConclusionsIn subjects with decompensated HFrEF, TIMP-1, but not MMP-9 was associated with the reverse remodelling in LVEF. In addition, patients with HFimpEF would have better long-term survival.